EXTENSIVE LISTENING: LET STUDENTS EXPERIENCE LEARNING BY OPTIMIZING THE USE OF AUTHENTIC MATERIALS - Hapsari, Yulia; Ratri, Devinta Puspita (Jurnal Pendidikan Bahasa dan Sastra, 2014)
In a country like Indonesia, one of challenges in learning English as a foreign language is a lack of exposure of English in its authentic sense. The use of authentic materials seems to be an option to cope with this situation. One of the ways to optimize the use of the authentic materials to trigger students to experience learning and to enhance their active involvement in the learning process is by using it in extensive listening activities. Through extensive listening by using authentic materials, students are exposed to real native speech in meaningful language use. As the result, difficulties in listening gradually disappear. Â In order to put the idea into practice, the first thing to do is to set objectives of each meeting based on core vocabulary and grammar that are suitable for the learners using comprehensible input principle as the basic consideration. Second, selecting authentic materials that suit the objectives and that give exposure to formulaic language and meaningful language use. Then, preparing activities in which the instruction is reasonable and lead to sufficient practice to develop fluency. Finally, synchronize teaching activities to increase studentsâ€™ motivation to learn. As a follow up activities, students are informed and eventually involved in the whole process. Thus, students experience learning and actively involved in their learning process.